2011
DOI: 10.1007/s00421-011-1978-0
|View full text |Cite
|
Sign up to set email alerts
|

South Pacific Islanders resist type 2 diabetes: comparison of aerobic and resistance training

Abstract: The purpose of this study was to evaluate the effectiveness of two exercise modalities for improving glycosylated hemoglobin (HbA1c) and associated clinical outcomes in Polynesian adults diagnosed with type 2 diabetes and visceral obesity. Twenty-six adults were randomized to receive resistance training or aerobic training, 3×/week, for 16 weeks. Dependent variables collected before and after intervention included: diabetes markers including HbA1c, blood lipids, relevant cytokines (C-reactive protein, adiponec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(138 citation statements)
references
References 18 publications
2
136
0
Order By: Relevance
“…However, upon reviewing the studies, it was impossible to perform this statistical procedure for the following reasons [19]:Seven studies presented pre- and posttreatment analytical data [2025], while four reported pre- and posttreatment delta variations [2629] and three studies presented some results in a graph form, without providing data that would enable this analysis [23, 24, 26]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, upon reviewing the studies, it was impossible to perform this statistical procedure for the following reasons [19]:Seven studies presented pre- and posttreatment analytical data [2025], while four reported pre- and posttreatment delta variations [2629] and three studies presented some results in a graph form, without providing data that would enable this analysis [23, 24, 26]. …”
Section: Resultsmentioning
confidence: 99%
“…The authors were asked via email to provide data required to perform the meta-analysis, but only one group [24] answered and sent the requested data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, a total of 14 trials (16 reports) extracted from 9,477 articles met the eligibility requirements and were included for the present systematic review and meta-analysis [15][16][17][18][19][20][31][32][33][34][35][36][37][38][39][40]. One study was excluded since it was not described as randomised [41], and two trials provided no information on whether the AET was supervised [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials reported random sequence generation [16,31,32,[36][37][38][39], and only five trials reported allocation concealment [16,31,32,37,38]. None of the studies reported the blinding of volunteers towards the mode of intervention (ESM Fig.…”
Section: Risk Of Biasmentioning
confidence: 99%